Enhancing Knowledge Sharing through Student Forums in a Learning Management System - Maulana Paramaditya Ananta; Muhammad Zidane Rizqy Alfain; Maulana Amirul Adha; Mari'atul Kamila Ramadhan; Isa Ansori (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2024)
This development study resulted in a Learning Management System (LMS) featuring a discussion forum as its primary component to support student learning activities. The forum serves to strengthen students’ knowledge sharing processes. The developed LMS is accessible via both web-based platforms and smartphones. The purpose of this development was to produce an LMS capable of facilitating discussion-based online learning and enabling students to share knowledge during the learning process. The resulting product was categorized as valid and feasible for use in online learning. Data were analyzed using both quantitative and qualitative approaches. The development model employed was the Web-based Instructional Design model proposed by Davidson-Shiver, Rasmussen, and Lowenthal. The LMS was declared valid and feasible for instructional use, as indicated by the media expert validation score of 97.22% and the subject matter expert validation score of 92.5%. Field trial results showed a feasibility score of 88.53%, and analysis of student feedback revealed predominantly positive responses. Overall, the Learning Management System was able to optimize the use of student discussion forums in strengthening knowledge sharing, particularly by facilitating direct interaction through discussion forums and video conferencing, allowing students to communicate, exchange ideas, and share knowledge effectively.